Functional assessment of the NMDA receptor variant GluN2AR586K [version 1; referees: 1 approved, 2 approved with reservations] - Katie F.M. Marwick; Peter Parker; Paul Skehel; Giles Hardingham; David J.A. Wyllie (Wellcome Open Research, 2017)
Background: The N-methyl-D-aspartate receptor (NMDAR) is an ionotropic glutamate receptor that has important roles in synaptogenesis, synaptic transmission, and synaptic plasticity. Recently, a large number of rare genetic variants have been found in NMDAR subunits in people with neurodevelopmental disorders, and also in healthy individuals. One such is the GluN2AR586K variant, found in a person with intellectual disability. Identifying the functional consequences, if any, of such variants allows their potential contribution to pathogenesis to be assessed. Here, we assessed the effect of the GluN2AR586K variant on NMDAR pore properties. Methods: We expressed recombinant NMDARs with and without the GluN2AR586K variant in Xenopus laevis oocytes and in primary cultured mouse neurons, and made electrophysiological recordings assessing Mg2+ block, single-channel conductance, mean open time and current density. Results: The GluN2AR586K variant was not found to influence any of the properties assessed. Conclusions: Our findings suggest it is unlikely that the GluN2AR586K variant contributes to the pathogenesis of neurodevelopmental disorder.